Effect of artificial seagrass on wave attenuation and wave run-up. Issue 1 (April 2016) - John, Beena Mary; Shirlal, Kiran G; Rao, Subba; Rajasekaran, C
Natural processes like wave action, tides, winds, storm surges, and tsunamis constantly shape the shoreline by inducing erosion and accretion. Coastlines with intact vegetated dunes, mangroves, and reefs act as a buffer zone against wave attack on beaches. This article discusses the effect of simulated seagrass on wave height attenuation and wave run-up through an experimental study. The tests were carried out with submerged artificial seagrass subjected to varying wave climate in a 50-m-long wave flume. Measurements of wave heights along the seagrass meadow and the wave run-up on a 1:12 sloped beach were taken for wave heights ranging from 0.08 to 0.16 m at an interval of 0.02 m and wave periods 1.8 and 2 seconds in water depths of 0.40 and 0.45 m.